- Specialized Rehabilitation of Military Personnel Convicted of Narcotics Crimes: A Normative Legal Study - Alfianti, Diana; Amrullah, M. Arief; Tanuwijaya, Fanny; Utomo, Hari (Al-Risalah, 2021)
This study focuses on the specialized rehabilitation of military personnel who have been convicted of narcotics crimes. Its aim was to comprehend the meaning, urgency, and concept of rehabilitating individuals within the military who have been found guilty of such crimes. To achieve this aim, the methodology used is normative legal study with statutory, contextual, case-based, and comparative approaches. Furthermore, the legal sources utilized consisted of both primary and secondary legislation. The results obtained from this study showed that rehabilitation for incarcerated military personnel involved in narcotic crimes corresponds to an endeavor aimed at providing exceptional rehabilitation specifically tailored to their circumstances. It is also important to note that the urgency of rehabilitation is closely related to the vested interest of the military in continuing the rehabilitation process, aligning with the initial recommendation. The state should, hence, give careful consideration to the implementation of specialized medical and social rehabilitation programs for military personnel who have been convicted of narcotic crimes. It is of utmost importance to establish a comprehensive framework within military agencies to facilitate the execution of medical and social rehabilitation measures for military members involved in narcotics offenses, including the necessary funding. In conclusion, the imposition of specialized rehabilitation measures, in conjunction with imprisonment, is essential for military personnel that are convicted of these crimes before their reintegration into society. This approach makes the state responsible for addressing the repercussions of their actions and providing tailored rehabilitation support to prevent any lingering resentment, minimize the risk of their recruitment by adversaries of the state, and enable their potential contributions if required in the future.